Increased aggregation with normal surface charge and deformability of red blood cells in children with nephrotic syndrome - Böhler, Thomas; Linderkamp, Otwin; Leo, Albrecht; Wingen, Anna-Margarete; Schärer, Karl (Clinical nephrology, 1992)
Hemorheological risk factors for thromboembolic disease were evaluated in 25 pediatric patients with idiopathic nephrotic syndrome (NS). In patients with increased proteinuria (greater than 100 mg/m2/24 h) red blood cell (RBC) aggregation and plasma viscosity were significantly increased when compared with patients in remission (less than 100 mg/m2/24 h) and with healthy controls. RBC surface charge was normal during increased proteinuria and remission. RBC aggregation correlated positively with plasma viscosity, fibrinogen, alpha 2-macroglobulin, immunoglobulin M, and the degree of proteinuria, and negatively with plasma albumin levels. RBC aggregation showed no correlation to RBC surface charge. Hematocrit and RBC deformability (rheoscope) were similar in both patient groups and in controls. Increased RBC aggregation and plasma viscosity may contribute to the increased risk of venous thromboembolism in NS.